Secretion-recapture process of apolipoprotein E in hepatic uptake of chylomicron remnants in transgenic mice. - Shimano, H (1994)
To investigate the role of apoE in hepatic uptake of chylomicron remnants, we studied chylomicron metabolism in transgenic mice overexpressing apoE in the liver. Plasma clearance of injected 125I-labeled human chylomicrons was fivefold faster in transgenic mice than in controls. Immunohistochemistry demonstrated that apoE was specifically localized at the basolateral surface of hepatocytes from fasted transgenic mice. After injection of a large amount of chylomicrons, the density of the cell surface apoE was markedly reduced and vesicular staining was observed in the cytoplasm, suggesting that the cell surface apoE was used for hepatic endocytosis of chylomicrons and remnants. Polyacrylamide gel analysis of chylomicrons and remnants that had been reisolated from plasma and from liver membrane after the injection of chylomicrons showed the particles to be enriched with apoE mainly after their influx into the liver rather than during their residence in plasma. These results provide strong evidence for the secretion-recapture process of apoE, whereby chylomicron remnants enter the sinusoidal space, acquire apoE molecules, and subsequently are endocytosed. Data from experiments with very low density lipoprotein and LDL showed that this system is specific for chylomicron remnants.